Hubungan Posisi Patella dan Tampa Scale Kinesiophobia Score dengan Single Hop Test dan IKDC Score pada Pasien Post Rekonstruksi ACL - Ngina Keo, Lydia Agusta; Pramita, Indah (PT. Kesehatan Gerak Fungsi Tubuh, 2025)
Background: Anterior cruciate ligament reconstruction (ACLR) is a surgical procedure to replace a torn or damaged ACL. However, long-term functional recovery is often hampered by fear of movement or re-injury (kinesiophobia), as measured by the Tampa Scale Kinesiophobia (TSK) Score. The aim of this study is to investigate the relationship between patella position, the level of kinesiophobia measured using the Tampa Scale of Kinesiophobia (TSK), functional performance assessed by the single hop testt, and subjective knee function evaluated through the International knee documentation committee (IKDC) score in patients after anterior cruciate ligament (ACL) reconstruction. Methods: This study used the literature review method. Article searches through PubMed and Google Scholar databases using the keywords Patella Position, TSK Score, Single Hop Test, IKDC Score and Post RACL Patients. Results: The six articles reviewed found a significant negative correlation between TSK Score and IKDC Score. High TSK Score tends to have low physical performance and poor IKDC Score. In addition, knee functional status and psychological preparedness play more of a role in determining quality of life than physical measures alone. Conclusion: There was a significant negative relationship between TSK Score and IKDC Score and single hop test performance. A high TSK Score affects physical functions such as the single hop test and a low IKDC Score. An unstable patellar position can be predicted using the Single Hop Test. These findings support the importance of a multidimensional approach in the comprehensive management of post-ACLR patients.